2020
DOI: 10.1101/2020.08.11.203117
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Redefining De Novo Gammaherpesvirus Infection Through High-Dimensional, Single-Cell Analysis of Virus and Host

Abstract: Virus infection is frequently characterized using bulk cell populations. How these findings correspond to infection in individual cells remains unclear. Here, we integrate high-dimensional single-cell approaches to quantify viral and host RNA and protein expression signatures using de novo infection with a well-characterized model gammaherpesvirus. While infected cells demonstrated genome-wide transcription, individual cells revealed pronounced variation in gene expression, with only 9 of 80 annotated viral op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
2
3
0
Order By: Relevance
“…S6b). This agrees with two recent studies that showed the single-cell heterogeneity in herpes simplex virus type 1 (HSV-1) infection 22 , and low correlation between viral gene expression in a murine gammaherpesvirus infection model 23 . One partial explanation is that the K8.1+ cells were at different stages of reactivation.…”
Section: Fd-seq Reveals Heterogeneity In Kshv Reactivated Single Tumosupporting
confidence: 92%
“…S6b). This agrees with two recent studies that showed the single-cell heterogeneity in herpes simplex virus type 1 (HSV-1) infection 22 , and low correlation between viral gene expression in a murine gammaherpesvirus infection model 23 . One partial explanation is that the K8.1+ cells were at different stages of reactivation.…”
Section: Fd-seq Reveals Heterogeneity In Kshv Reactivated Single Tumosupporting
confidence: 92%
“…6a). This agrees with two recent studies that showed heterogeneity in host cell factor abundance at the single-cell level in herpes simplex virus type 1 (HSV-1) infection 24 , and low correlation in expression of viral genes in a murine gammaherpesvirus infection model 25 . This may partially be caused by the possibility that the sorted K8.1+ cells were at different stages of reactivation.…”
Section: Resultssupporting
confidence: 92%
“…It is notable that while the LANA protein is expressed throughout infection, it is generally expressed at a low level, and thus, combination with the enzymatic amplification of beta-lactamase is critical. Further development of this beta-lactamase tagged virus system allowed tracking of cells infected with panels of mutant viruses both in vitro and in vivo, as well as live cell sorting of rare infected cells for downstream analyses of function and multiparametric mass cytometry and transcriptomics (25, 26).…”
Section: Introductionmentioning
confidence: 99%